Kort historia över finsk-rysk lexikografi - Tuomola, Hannu (LexicoNordica, 2004)
This paper gives a short survey of the development of Russian ↔ Finnish lexicography from the first Russian-Finnish and Finnish-Russian dictionary to the mast recent ones. Apart from a general outline of the mast important lexicographic data in this connection, an analysis of the rnicro- and macrostructure of same of the mast important dictionaries is presente?